Citrus Production in Argentina - Futch, Stephen; Singerman, Ariel (EDIS, 2017)
Argentina has a very dynamic citrus industry. Citrus is grown in 10 out of 23 provinces. The important citrus varieties in terms of planted area are lemons, oranges, mandarins and grapefruit. In 2015, Argentina had 326,216 acres devoted to citrus. The country produced 63.5 million boxes of citrus in 2015–16, making Argentina the world’s ninth largest citrus-producing country. Argentina’s lemon production represents nearly 85 percent of that in the Southern Hemisphere and 22 percent of the world’s production. The planted area for oranges and grapefruit is decreasing because growers are increasing acreage devoted to lemon production. Such shifts are due to market and economic reasons mainly driven by the high value of byproducts (i.e., essential oils).